2021
DOI: 10.1097/icl.0000000000000828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Topical Povidone-Iodine and Antibiotic Applications on Meibomian Glands and Ocular Surface Parameters in Patients With Repeated Intravitreal Injections

Abstract: Objectives: To assess whether meibomian glands and ocular surface parameters are affected by repeated topical povidone-iodine and antibiotic applications in patients with repeated intravitreal injections. Methods: Forty-five patients with at least three previous intravitreal injections and 28 healthy controls were included in the study. In the injection group, 21 patients had age-related macular degeneration and 24 patients had diabetic macular edema. For each participant, infrared meibography for the upper an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In both studies, TBUT was found to be decreased in eyes that received injections, in line with our results. 10,11 The Oxford ocular surface staining score was examined by Saedon et al 9 in patients with unilateral intravitreal injection and was reported to be significantly higher in the injected eye than in the fellow eye, similar to our study. In another study, Kim et al 26 reported that Rose Bengal staining and corneal fluorescein staining increased after 5% PVI exposure in rabbit eyes, while the Schirmer test was not affected.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In both studies, TBUT was found to be decreased in eyes that received injections, in line with our results. 10,11 The Oxford ocular surface staining score was examined by Saedon et al 9 in patients with unilateral intravitreal injection and was reported to be significantly higher in the injected eye than in the fellow eye, similar to our study. In another study, Kim et al 26 reported that Rose Bengal staining and corneal fluorescein staining increased after 5% PVI exposure in rabbit eyes, while the Schirmer test was not affected.…”
Section: Discussionsupporting
confidence: 88%
“…In these limited number of studies, it was commonly observed that patients' quality of life was significantly affected. 9–11,18 In our study, the IVI group had a significantly higher OSDI score of 36.81±19.49 when compared with the control group. Although the OSDI score of the NIVI group was 29.31±17.5, which was lower than that of the IVI group, there was no significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations